REPAIR PROCEDURE FOR DAMAGE TO V PROSEDUR PERBAIKAN ATAS KERUSAKAN PERALATAN VHF-A/G MERK OTE DT100 FREKUENSI 124.2 MHZ CABANG YOGYAKARTA – YOGYAKARTA INTERNATIONAL AIRPORT - Permatasari, Chintya (Cipta Kind Publisher, 2024)
In the communication system, it has an impact on the ease of conveying information, one of which is the application in communication between aircraft and outside parties and between aircraft themselves The occurrence of communication within visibility allows pilots/co-pilots to use VHF radio communication between aircraft and aircraft or aircraft and ground stations. VHF radio communication system will emit and receive Amplitude Modulation radio signals with different frequency ranges, namely 118 MHz to 136,975 MHz VHF Air Ground Tower Set is an aviation communication facility used for communication between aircraft in the air and aviation traffic control officers on the ground for the purposes of regulating aviation traffic at an airport whose regulation is carried out by visual observation VHF Air Ground Tower Set is a unified system of aviation communication equipment in aviation traffic control towers consisting of several systems, VHF Transmitter and Receiver VHF Air Ground or Tower Set is an aviation communication facility used for communication between aircraft in the air and flight traffic controllers on the ground for the purpose of regulating flight traffic at an airport where the regulation is carried out by visual observation.